EL Impacto de la inteligencia artificial en el marketing digital: revisión sistemática de la literatura - Ramirez Agreda, Maria Rosa (2025)
Artificial intelligence has become a transformative technology in digital marketing due to the various benefits it offers. Therefore, the objective of this research is to analyze the main positive and negative effects that arise from the incorporation of emerging technologies such as artificial intelligence in the field of digital marketing. This systematic review followed the PRISMA method guidelines, successfully identifying 39 relevant articles out of more than 10,000 studies found across various databases such as Scopus, Dimensions, Web of Science, and Google Scholar. Furthermore, through a thorough bibliometric analysis, several thematic clusters were identified, including artificial intelligence, digital marketing, social media, consumer behavior, technology adoption, decision-making, CRM, and ethics. These keywords helped us understand the existing trends within the studied field. The conclusion drawn from the findings is that AI strongly influences consumer behavior through personalization; however, there are significant challenges regarding data privacy, transparency, and ethics that must be addressed to avoid compromising consumer privacy.